(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The implementation of individualized educational technologies has become an essential strategy for improving the quality of educational-corrective services provided to learners with visual impairments. However, empirical evidence regarding the effectiveness of these technologies in promoting both academic achievement and social competence remains limited. This study evaluates the effectiveness of individualized educational technologies in enhancing the academic and social competencies of learners with visual impairments within specialized educational institutions. A mixed-methods research design was employed, combining pedagogical experimentation, classroom observation, diagnostic assessment, teacher interviews, questionnaires, and statistical analysis. The empirical investigation involved 151 primary-level learners with visual impairments enrolled in specialized educational institutions in Uzbekistan. Individualized educational technologies were implemented through differentiated instruction, adaptive learning materials, assistive educational resources, individualized developmental planning, and continuous pedagogical and psychological support. The effectiveness of these technologies was assessed using indicators of academic engagement, communication competence, learning motivation, independent learning skills, and social adaptation. The results demonstrate that learners who participated in the individualized educational program showed measurable improvements across all evaluated dimensions.